Down‐regulation of circDMNT3B is conducive to intestinal mucosal permeability dysfunction of rats with sepsis via sponging miR‐20b‐5p - Liu, Jiao (J Cell Mol Med, 2020)
Sepsis is a life‐threatening syndrome with a high risk of mortality, which is caused by the dysregulated host response to infection. We examined significant roles of circDMNT3B and miR‐20b‐5p in the intestinal mucosal permeability dysfunction of rats with sepsis. SD rats were randomly divided into 6 groups (n = 10/group): sham group, sepsis group, si‐negative control group, circDNMT3B‐si1 group, circDNMT3B‐si2 group and circDNMT3B‐si1 + anti‐miR‐20b‐5p group. The level of malondialdehyde (MDA) content, superoxide dismutase (SOD) activity, interleukin (IL)‐6 and IL‐10 levels were measured through ELISA assay kits. Cell survival rate and cell apoptosis were evaluated by Cell‐Counting Kit‐8 Assay and flow cytometry, respectively. Luciferase reporter assays were used to investigate interactions between miR‐20b‐5p circDMNT3B in HEK‐293T cells. Silencing circDNMT3B can significantly increase the level of d‐lactic acid, FD‐40, MDA, diamine oxidase, IL‐10 and IL‐6, compared with sepsis group, while the SOD activity was lower. Silencing circDNMT3B leads to oxidative damage and influence inflammatory factors level in intestinal tissue. CircDNMT3B was identified as a target gene of miR‐20b‐5p. Silencing circDNMT3B decreased cell survival and induced apoptosis in Caco2 cells treated with LPS, which was reversed by anti‐miR‐20b‐5p. MiR‐20b‐5p inhibitor remarkably down‐regulated mentioned‐above levels, in addition to up‐regulate SOD activity, which may relieve the damage of intestinal mucosal permeability caused by silencing circDNMT3B in sepsis rats. Down‐regulation of circDMNT3B was conducive to the dysfunction of intestinal mucosal permeability via sponging miR‐20b‐5p in sepsis rats, which may provide the novel strategy for sepsis treatment in the future.